Identity Resilience and Professional Project Reconstruction Among Internally Displaced Youth: The Case of Young People Settled in the Central Region of Burkina Faso - Dakuyo, Elie Corneille (European Scientific Journal, ESJ, 2025)
This qualitative study examines the processes of identity resilience and professional project reconstruction among internally displaced youth settled in the central region of Burkina Faso. In a context of security crisis that has caused the displacement of more than 2 million people since 2016, this research focuses specifically on the adaptive mechanisms developed by young people aged 18 to 30 to reconstruct their professional identity after a major biographical rupture. The methodological approach is based on semi-structured interviews conducted with 25 internally displaced youth, analyzed using a thematic analysis approach inspired by grounded theory. The results reveal three central processes of identity reconstruction: narrative reappropriation of life trajectory, creative adaptation to new professional opportunities, and mobilization of community and family resources. The study highlights the importance of psychosocial protective factors in the development of identity resilience, particularly social support, access to professional training, and recognition of skills acquired through adversity. These results contribute to a better understanding of identity reconstruction processes in crisis contexts and offer perspectives for psychological support of displaced populations.